2011
DOI: 10.1038/jhg.2011.137
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage analysis in families with infantile hypertrophic pyloric stenosis indicates novel susceptibility loci

Abstract: Infantile hypertrophic pyloric stenosis (IHPS) is a common cause of upper gastrointestinal obstruction during infancy. A multifactorial background of the disease is well established. Multiple susceptibility loci including the neuronal nitric oxide synthase (NOS1) gene have previously been linked to IHPS, but contradictory results of linkage studies in different materials indicate genetic heterogeneity. To identify IHPS susceptibility loci, we conducted a genome-wide linkage analysis in 37 Swedish families. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Differences across population subjects in allelic frequency and linkage disequilibrium also allow for contrasting results. Analyses of DNAs obtained from three Swedish families with multiple affected members did not correlate with NOS1 locus ( Söderhäll & Nordenskjöld, 1998 ); however, a study of 37 Swedish vs 31 British families with IHPS suggested positive correlation ( Svenningsson et al, 2012 ). The major limitation of all studies was the limited number of subjects used.…”
Section: Survey Methodologymentioning
confidence: 85%
“…Differences across population subjects in allelic frequency and linkage disequilibrium also allow for contrasting results. Analyses of DNAs obtained from three Swedish families with multiple affected members did not correlate with NOS1 locus ( Söderhäll & Nordenskjöld, 1998 ); however, a study of 37 Swedish vs 31 British families with IHPS suggested positive correlation ( Svenningsson et al, 2012 ). The major limitation of all studies was the limited number of subjects used.…”
Section: Survey Methodologymentioning
confidence: 85%
“…More detailed analysis was carried out for the following CA: CDH, EA, omphalocele (OM), gastroschisis (GS), omphalomesenteric duct (OMD), duodenal atresia (DA), intestinal atresia (IA) (jejunal/ileal/colonic), infantile hypertrophic pyloric stenosis (IHPS), Hirschsprung disease (HSCR), anorectal malformation (ARM), bladder exstrophy (BE), and posterior urethral valve (PUV). Although the recognition that IHPS is acquired and not a congenital disorder is increasing, the genetic background of isolated IHPS has been described in several studies, [15,16] contributing to the classification of IHPS as a congenital disorder in the present study. Clinical data were gathered from the medical records of patients undergoing surgical treatment for selected major gastrointestinal, muscular, orgenitourinary CA during the study period.…”
Section: Methodsmentioning
confidence: 87%
“…Different than for EA, there has been reported a male predominance for IHPS (4:1) (MacMahon, 2006). There have been risk loci associated to IHPS (Everett & Chung, 2013; Fadista et al, 2019; Feenstra et al, 2012; Feenstra et al, 2013; Svenningsson et al, 2012). To date, no risk loci have been described for EA.…”
Section: Discussionmentioning
confidence: 99%